Research on clustering algorithm based 6G typical usage scenarios - Ning JIN; Qingyang WANG (Dianxin kexue)
Compared with the three classic 5G usage scenarios, the content and types of 6G typical usage scenarios will be more abundant and diverse.How to refine 6G usage scenarios objectively and efficiently has become a major challenge.Based on this, the clustering algorithm was used to study the 6G usage scenarios.Firstly, the 6G service and performance indicators were considered.Then, the demand values of 6G service were collected and the indicators were scored.Finally, the sample data were analyzed by different clustering algorithms.According to the clustering results, eight typical usage scenarios of 6G were proposed, which could provide some reference for 6G research in the industry.